2009
DOI: 10.4321/s1130-01082009001100002
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Helicobacter pylori and mechanisms of clarithromycin resistance in strains isolated from patients in Uruguay

Abstract: The prevalence and mechanisms of antibiotic resistance of Helicobacter pylori have not yet been investigated in Uruguay. The objective of this study was to assess the susceptibility of H. pylori to the most frequently used antibiotics and to determine the mechanism of resistance to clarithromycin. Seventy-nine isolates were obtained from gastric biopsies of 50 adult patients during two periods, 2001 and 2006. The former group enrolled the general population (GP), the latter group Afro-descendant (AD) subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…No AMO-resistant strains were identified in this study, this is most frequently reported with AMO where failure is rarely caused by acquired resistance [49, 50]. Other mutations at position 2142 (A-to-G transition) and position 2182 (C-to-T transition) have been confirmed by analysis of DNA sequencing to be the same as that described at position 2143 and are associated with CLA resistance [51].…”
Section: Antibiotic Resistance Mechanisms In the Current Regimenssupporting
confidence: 51%
“…No AMO-resistant strains were identified in this study, this is most frequently reported with AMO where failure is rarely caused by acquired resistance [49, 50]. Other mutations at position 2142 (A-to-G transition) and position 2182 (C-to-T transition) have been confirmed by analysis of DNA sequencing to be the same as that described at position 2143 and are associated with CLA resistance [51].…”
Section: Antibiotic Resistance Mechanisms In the Current Regimenssupporting
confidence: 51%
“…The global average mutation frequency for the A2143G and A2142G mutations are 69.8% and 11.7%, respectively (23). In many studies, the point mutations A2142G (13,18,23,24) and/or A2142C (4,13,21,24) were not found, and numerous investigations reported that A2143G was the only detected mutation or the most prevalent (4,5,13,17,18,(21)(22)(23)(24)(25). On the other hand, it has been found that the presence of the A2143G point mutation, but not of A2142G or A2142C, significantly lowered the H. pylori eradication rate (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the main resistance to metronidazole has been attributed to frequent use of this drug, which is regularly prescribed for other diseases and infections. For this reason, metronidazole has been omitted from first-line experiential therapy strategies in some countries (15). Prolonged amoxicillin-based standard triple therapy was recommended by the European guidelines for countries with > 40% metronidazole resistant H. pylori strains (16).…”
Section: Discussionmentioning
confidence: 99%